PENDIDIKAN AGAMA ANAK SUKU KALANG - Misbah Zulfa Elizabeth (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2011)
This study with descriptive qualitative approach produces a fact that the context of education, the children of the Kalang community in general are also followed formal education, like other school children. They also received religious instruction as a compulsory subject. This of course has consequences for the possibility of cultural transformation through the instrument of education. Especially with religious education, the children of the Kalang community possible simultaneously and slowly will leave their teachings. Moreover, the nature of religious education itself is more of an orthodox religious values.